The Effect of Combination of Breast Massage and Oxytocin Massage on Breast Milk Production in Primiparous Postpartum Mothers - Ernawati, Dewi; Ani, Murti; Muyassaroh, Yanik (Journal of Midwifery Science: Basic and Applied Research, 2024)
Indonesia's exclusive breastfeeding coverage in 2023 was recorded at only 67.94%, down from 67.96% in 2022. The low coverage of exclusive breastfeeding for babies is caused by several factors, one of which is a lack of breast milk production in the breasts.The aim of this research is to analyze the effect of a combination of breast massage and oxytocin massage on breast milk production in primiparous postpartum mothers in Kapuan Village, Blora Regency in 2024.This research is a quasi-experimental study with one pre-test and post-test with control group. The population of this study was 30 primiparous postpartum mothers at the Kapuan Community Health Center in October - December 2024 with the number of samples taken using the total sampling method. Data was measured using a pretest, namely measuring breast milk production, carried out on the 8th day of postpartum and the posttest carried out on the 10th day. Measurement of breast milk production was carried out 3 times, namely at 7, 8, 9. Intervention (a combination of breast massage and oxytocin massage) was carried out for 2 days. , one session for 15 minutes. The research was carried out in October – December 2024. The research instrument used a questionnaire. Data analysis used the Mann Whitney U test.The average breast milk production in the pretest intervention group was 77.67 ml, while in the control group it was 76.67 ml. The average breast milk production in the posttest intervention group was 92.33 ml, while in the control group it was 78.0 ml. The Kruskal-Wallis results obtained a significance value of 0.000 (p0.05), thus it was concluded that there was an effect of the combination of breast massage and oxytocin massage on breast milk production in primiparous postpartum mothers at the Kapuan Health Center, Blora Regency